THE INFLUENCE OF VIRTUAL TOUR ON VISIT INTENTION IN NATIONAL MUSEUM OF INDONESIA - Shaula Keumala; Haryadi Darmawan; Tatang Sopian (International Journal of Sustainable Competitiveness on Tourism, 2022)
Ministry of Tourism and Creative Economy attempted tourism recovery after Covid-19 outbreak that rippled throughout the world by developing Virtual Tour which was implemented by travel agents and many tourism destinations in Indonesia, including the National Museum of Indonesia. In this study, the researcher aimed to identify the performance of Virtual Tour in the National Museum of Indonesia and to see whether it influences the tourists' visit intention. Using a quantitative research approach and explanatory research method, the researcher collected samples from 150 tourists within August 3rd – 16th 2021 who had previous experiences with the Virtual Tour in the National Museum of Indonesia. through online questionnaire distribution. The technique used was convenience sampling that later would be processed with simple linear regression. Samples taken through online questionnaire distribution in this study were then collected and analyzed using a classical assumption test. The results of this study indicated that the Virtual Tour to the National Museum of Indonesia is perceived as useful, entertaining, and easy to use and Virtual Tour has a 6.2% influence on Visit Intention to the National Museum of Indonesia.